Asrâr al-Mutasyâbih al-Lafdzî Fi al-Qur’an ‘Inda Ibnu al-Zubair al-Gharnathi - Rochmad; Putra, Muhammad Perdana (Studia Quranika, 2017)
Al-Qur'an is a revelation to Muhammad Saw. as a miracle. Miracles of the Qur'an which are located in a typical sentence structure and full of literary style. Among the peculiarities of wording in the verses of the Qur'an is seen some repetition of similar wording in some places. According to some people, especially the enemies of Islam that it is worthless. Though the scholars see that it is precisely here that the miracles of the Qur'an, so that there are several related works al-mutasyâbih al-lafdzî this, among them the works of Imam al-Zarkasyi, al-Suyuti, al-Sakkhawi, Abdullah al-Razi , Badrun Din al-Qadhi, and according to the best scholars is Ibn al-Zubair al-Gharnathi. The study only focused on the al-Nisâ to see a secret al-mutasyâbih al-lafdzi according to al-Gharnathi. Thus was discovered that al-mutasyâbih al-lafdzî the Qur'an has several forms, namely editorial similarities in some sentences just by the turn of a few sentences with a similar sentence, or replacement of letters with other letters, some of which are in the form of additions or reductions word or phrase, put the phrase or word that should be behind in a set, then the last one is to hide or even remove certain words or phrases when the sentence is in the other place. While secret al-mutasyâbih al-lafdzî the Qur'an by al- Gharnathi is that the replacement word or phrase to indicate a secret that in turn is related, as the khalaqa which later became ja'ala in a different wording , Then there was the addition to strengthen and clarify the previous phrase in a sentence. Putting a sentence or a word that should be behind in an order to show the beauty of the wording of the Qur'an as well as showing the main purpose of a sentence. While hide or even remove certain words or phrases is to facilitate the reading of the Qur'an.